Predictive role of left atrial and ventricular mechanical function in postoperative atrial fibrillation: a two-dimensional speckle-tracking echocardiography study - TİGEN, MUSTAFA KÜRŞAT (TURKISH SOC CARDIOLOGY, 2016)
Objective: The aim of this study was to determine the role of left-sided mechanical parameters in postoperative atrial fibrillation (POAF) in patients undergoing coronary artery bypass grafting (CABG). Methods: Ninety patients with coronary artery disease and normal left ventricular (LV) function in sinus rhythm were enrolled in the study. Preoperative LV and left atrial (LA) mechanics were evaluated by two-dimensional (2D) speckle-tracking echocardiography (STE), including strain and rotation parameters, and volume indices. Patients were monitored in order to detect POAF during the postoperative period. Results: Twenty-three of 90 patients (25.6%) developed POAF. Age (p<0.001) and preoperative beta blocker usage (p=0.001) were the clinical parameters associated with POAF. Left atrial maximum volume index (LAV[max]i) increased, and peak left atrial longitudinal strain (PALS) was impaired in POAF patients (p=0.001, p<0.001, respectively). Left ventricular twist (LVtw) and left ventricular peak untwisting velocity (UntwV) were augmented in POAF patients (p=0.013, p=0.009, respectively). Receiver operating characteristic analysis showed N-terminal pro-brain natriuretic peptide (NT-proBNP) levels above 70 pg/ml and predicted POAF with a sensitivity of 74% and specificity of 78% (area under curve: 0.758, 95% confidence interval [CI] 0.631-0.894, p<0.001). Logistic regression analysis demonstrated that age (odds ratio [OR] 1.1, CI 1.01-1.20, p=0.034), preoperative beta blocker usage (OR 8.84, CI 1.36-57.28, p=0.022), NT-proBNP (values >70 pg/ml, OR 22.377, CI 3.286-152.381, p<0.001), PALS (OR 0.86, CI 0.75-0.98, p=0.023), and UntwV (OR 1.02, CI 1.00-1.04, p=0.029) were the independent predictors of POAF. Conclusion: The combination of 2D STE, clinical, and biochemical parameters may help predict POAF.
Keywords: Atrial fibrillation; coronary artery disease; left atrial strain; left ventricular strain; speckle tracking echocardiography; CORONARY-ARTERY-BYPASS; NATRIURETIC PEPTIDE; CARDIAC-SURGERY; DIASTOLIC DYSFUNCTION; STRAIN; HEART; DETERMINANTS; DYSSYNCHRONY; ASSOCIATION; ARRHYTHMIAS